Preanalytical Confounding Factors in the Analysis of Cerebrospinal Fluid Biomarkers for Alzheimer’s Disease: The Issue of Diurnal Variation - Cicognola, Claudia; Chiasserini, Davide; Parnetti, Lucilla (Frontiers in Neurology, 2015)
Given the growing use of cerebrospinal fluid (CSF) beta-amyloid (Aβ) and tau as biomarkers for early diagnosis of Alzheimer’s disease (AD), it is essential that the diagnostic procedures are standardized and the results comparable across different laboratories. Preanalytical factors are reported to be the cause of at least 50% of the total variability. Among them, diurnal variability is a key issue and may have an impact on the comparability of the values obtained. The available studies on this issue are not conclusive so far. Fluctuations of CSF biomarkers in young healthy volunteers have been previously reported, while subsequent studies have not confirmed those observations in older subjects, the ones most likely to receive this test. The observed differences in circadian rhythms need to be further assessed not only in classical CSF biomarkers but also in novel forthcoming biomarkers. In this review the existing data on the issue of diurnal variations of CSF classical biomarkers for Alzheimer’s disease will be analyzed, also evaluating the available data on new possible biomarkers.